An assessment of the ex-post socio-economic impacts of global rinderpest eradication: Methodological issues and applications to rinderpest control programs in Chad and India - Rich, Karl M.; Roland-Holst, D.; Otte, J. (Elsevier, 2014)
Rinderpest was once one of the world’s most feared diseases of livestock, responsible for the deaths of millions of livestock. However, rinderpest is just one of two diseases that has been successfully eradicated globally. A major gap in the history of rinderpest concerns the socio-economic impacts of its control and eradication. While much has been documented on the epidemiological, technical, and institutional lessons resulting from rinderpest control and prevention, very little has been written on the implications for society at local, national, regional and global levels. In this paper, we provide a more rigorous methodological approach to the estimation of the global impact of rinderpest eradication that highlights the different levels of impacts and benefits associated with different groups of stakeholders. Our methodology is applied to the cases of Chad and India.